Case report and review of the literature: the utilisation of a ventricular assist device as bridge to recovery for anthracycline-induced ventricular dysfunction. (4th December 2017) - Krasnopero, Diane; Asante-Korang, Alfred; Jacobs, Jeffrey; Stapleton, Stacie; Carapellucci, Jennifer; Dotson, Mathew; Stapleton, Gary
Abstract: Ventricular assist devices are used in children with heart failure as a bridge to myocardial recovery or cardiac transplantation. Anthracyclines cause cardiac toxicity and may result in acute or long-term cardiac failure. We describe the use of a ventricular assist device as a bridge to recovery in a child with severe acute anthracycline-induced cardiomyopathy, and we review the associated literature. A 6-year-old girl was treated for acute myeloblastic leukaemia with daunorubicin and mitoxantrone. After 2 weeks her final dose of chemotherapy, her Left Ventricular Ejection Fraction decreased to 21%. Despite initiation of medical therapy, she had continued deterioration of left ventricular function and developed evidence of poor end-organ perfusion. She was not a candidate for cardiac transplantation, as the post-transplant immune suppression therapy would put her at risk for recurrence of her malignancy. We placed her on a short-term ventricular assist device as a bridge to ultimately placing her on a long-term ventricular assist device versus continuing medical therapy. Her left ventricular ejection fraction improved to 55% 24 days after ventricular assist device insertion. She was separated from the ventricular assist device 26 days after its insertion. She was discharged home 29 days later and is now 28 months after ventricular assist device implantation with stable ventricular function, as documented by a left ventricular ejection fraction of 55%, and normal end organ function. This case is one of the only reports known describing successful use of a short-term ventricular assist device as a bridge to recovery in a child with severe acute anthracycline-induced cardiotoxicity.